Improvement of Earthquake Mitigation Ability using Earthquake Safety Tips Mobile Game of Students with Intellectual Disability in Special School - Putri, Aulia; Junaidi, Ahsan Romadlon; Kurniawan, Agung (Angstrom Centre of Education, 2023)
It is important to teach students with intellectual disability about earthquake mitigation because they belong to vulnerable groups of earthquake threats. Qualified learning media is needed to train the earthquake mitigation ability of students with intellectual disability. This study aims to determine the improvement of earthquake mitigation ability using Earthquake Safety Tips mobile game of students with intellectual disability in Special School. The research design used a pre-experimental one-group pretest-posttest design and used Wilcoxon matched pairs as an analysis method. The results showed there is increasing score from pre-test to post-test on each aspects of earthquake mitigation ability, which are cognitive, affective, and psychomotor ability. The hypothesis test shows that there is significant difference in cognitive ability which is 0,027 < 0,05, affective ability obtained 0,011 < 0,05, and psychomotor ability obtained 0,012 < 0,05. In conclusion, earthquake mitigation drill using Earthquake Safety Tips mobile game could improve the earthquake mitigation ability of students with intellectual disability in Special School.